Kaposi´s sarcoma, epidemic type. Case presentation - Gilberto Serrano Ocaña; Juan Carlos Ortiz Sablon; Ilen Ochoa Tamayo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Before the AIDS epidemic, Kaposi's sarcoma was found mainly in elderly men of Mediterranean coast, eastern European background and Jewish ancestry (rarely in older women) and is a slow growing skin tumor. In AIDS patients, the KS tends to develop more rapidly compromising the skin, lungs, gastrointestinal tract and other organs. In people with AIDS, Kaposi's sarcoma is caused by an interaction between HIV, a weakened immune system and human herpes virus 8. It affects approximately 20% of people with HIV that don't take antiretroviral drugs. It is more common in homosexual's patients, but may appear in any HIV positive individual, in Africa where heterosexual HIV transmission route is the most important can also be found in children and women. We are presenting a case of Kaposi sarcoma in a young female admitted at the Internal Medicine Department of Dora Nginza Hospital.